1988
DOI: 10.1002/hep.1840080526
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis D virus RNA in acute delta infection: Serological profile and correlation with other markers of hepatitis D virus infection

Abstract: To evaluate the profile of hepatitis D virus replication and the corresponding immunoresponse after acute hepatitis D virus infection, sera from 50 patients with acute hepatitis D (36 with acute hepatitis B virus-hepatitis D virus coinfection and 14 HBsAg carriers with hepatitis D virus superinfection) were investigated for the presence of hepatitis D virus RNA and other serological hepatitis D virus markers. During the first week after onset of symptoms, hepatitis D virus RNA was detected by spot hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 11 publications
0
25
0
1
Order By: Relevance
“…Recent studies in patients with orthotopic liver transplantation support this view; HDV can establish latent, nonpathogenic infections on the graft and that reactivation of these infections to disease depends on HBV replication [8,24]. Intrahepatic HDAg, serum IgM anti-HDV and serum HDV-RNA detectable by dot-blot hybridization are excellent markers for active HDV replication [2,15,27]. Classical studies have suggested that the mechanism of liver damage in HDV infection is directly cytopathic.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies in patients with orthotopic liver transplantation support this view; HDV can establish latent, nonpathogenic infections on the graft and that reactivation of these infections to disease depends on HBV replication [8,24]. Intrahepatic HDAg, serum IgM anti-HDV and serum HDV-RNA detectable by dot-blot hybridization are excellent markers for active HDV replication [2,15,27]. Classical studies have suggested that the mechanism of liver damage in HDV infection is directly cytopathic.…”
Section: Discussionmentioning
confidence: 95%
“…The sensitivity of the assay was later improved significantly by using longer radiolabeled RNA probes (185) produced by in vitro transcription. Several investigators showed that persistence of HDV RNA in serum may indicate a progression to chronicity (25,217). A method for detecting intrahepatic HDV RNA in frozen and formalin-fixed sections by in situ hybridization has also been developed (85); however, this assay does not appear to be more sensitive than the direct IF assay for HDAg.…”
Section: Methods Of Detecting Hdvmentioning
confidence: 99%
“…153,154 In self-limited HDV/HBV coinfection, serum markers of HDV infection can be transient and therefore diffucult to detect (Figure 3). 153,155,156 Markers of HDV infection that appear early in acute coinfection, within 1 to 10 days of the onset of symptoms, include serum HDAg 149, 153,155,156 and HDV RNA 146,149,153,[155][156][157] (Table 3). Anti-HD IgM appears 2 to 3 weeks after the onset of symptoms.…”
Section: A Diagnosis Of Acute Delta Hepatitismentioning
confidence: 99%
“…Serum HDV RNA is a very sensitive early marker of HDV infection, and can be detected by slot-blot hybridization. [144][145][146][147][148][149][150][151][152][153][154][155][156][157] As few as 10 4 to 10 6 genomes can be detected using this simple assay. 159 When tests to detect serum HDAg and HDV RNA are not available for clinical purposes, HDV infection is confirmed somewhat after the fact by detection of total anti-HD Ab by competitive microplate assay.…”
Section: A Diagnosis Of Acute Delta Hepatitismentioning
confidence: 99%